2020
DOI: 10.1152/ajpheart.00308.2019
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 mediates ischemia-reperfusion-induced cardiomyocyte apoptosis via MCPIP1 and CaSR

Abstract: Monocyte chemotactic protein-1 (MCP-1) plays a crucial role in ischemia-reperfusion (I/R) injury; however, the detailed mechanism of MCP-1 in I/R injury-induced cardiomyocyte apoptosis remains unclear. In this study, we explored the cascade downstream of I/R-induced MCP-1 that modulates cell apoptosis and determined whether Ca2+-sensing receptors (CaSRs) are involved in the process. Protein levels were detected in a cardiac muscle cell line (HL-1) and primary cultured neonatal mouse ventricular cardiomyocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…It has also been suggested that CCL2 may exert direct actions on cardiomyocytes, increasing injury-associated death and promoting dysfunction. Some studies have suggested that CCL2 may promote cardiomyocyte apoptosis through induction of the ribonuclease monocyte chemoattractant protein-1-induced protein (MCPIP, originally proposed to function as a transcription factor), also known as regnase-1 [ 145 , 146 ]. However, regnase-1/MCPIP can be induced by a wide range of inflammatory mediators, and is known to restrain inflammation by degrading cytokine RNAs in immune and non-immune cells [ 147 ].…”
Section: Ccl2 and The Chemokinesmentioning
confidence: 99%
“…It has also been suggested that CCL2 may exert direct actions on cardiomyocytes, increasing injury-associated death and promoting dysfunction. Some studies have suggested that CCL2 may promote cardiomyocyte apoptosis through induction of the ribonuclease monocyte chemoattractant protein-1-induced protein (MCPIP, originally proposed to function as a transcription factor), also known as regnase-1 [ 145 , 146 ]. However, regnase-1/MCPIP can be induced by a wide range of inflammatory mediators, and is known to restrain inflammation by degrading cytokine RNAs in immune and non-immune cells [ 147 ].…”
Section: Ccl2 and The Chemokinesmentioning
confidence: 99%
“…Indeed, recent studies reported the expression and release of Ccl2 from cardiomyocytes in response to I/R by inflammatory mediators. 36,37…”
Section: Resultsmentioning
confidence: 99%
“…We identified the monocyte-attracting chemokine Ccl2 as a target regulated by the mTORC1-4EBP1-eIF4F pathway that was expressed by a subset of cardiomyocytes exclusively in response to reperfusion, as has been recently described for isolated cardiomyocytes. 36,37 Inhibition of the CCR2-CCL2 axis was previously shown to exhibit beneficial effects in murine models of myocardial infarction. 48 In addition, mTORC1 was previously described to regulate (which was not certified by peer review) is the author/funder.…”
Section: Translational Regulation Of Myocardial Inflammation In Respo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the migration pathway of chemotactic PMN to the site of myocardial injury cannot be fully described, the role of PMN activation in the pathogenesis of cardiovascular disease is clear. PMN was recruited to the infarct area very early, they play a role by adhering to vascular endothelial cells through molecules of selectins, integrins and immunoglobulin superfamily [39]. Once adhered to the infarct area, PMN will release ROS, cytokines and proteolytic enzymes, resulting in the increase of MDA level and the decrease of SOD level [40].…”
Section: Discussionmentioning
confidence: 99%